Quran Apps in Playstore: The Problem of Authentication and Religious Authority - Kushidayati, Lina (FIKRAH, 2019)
This article discuss about an application at Google Play Store that appears along with the rise of smartphone usage. It's also take effect to Muslims live style and religious practice, for example in reading Quran.  There are many Quran applications are available on the Play store, its raises questions on religious authorities because anyone can upload an Android-based Quran application on the Play store. A descriptive qualitative approach use to analyze Qur’an apps in Google Play store. The apps are chosen based on the numbers of download and comments from the users. The results show that the growth of digital Quran applications raises new styles of worship such as reading the Quran on smarthphone application.